Pengaruh Kualitas Audit, Debt Default Dan Pertumbuhan Perusahaan Terhadap Penerimaan Opini Audit Going Concern - Riyanto Setiawan Suharsono (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2018)
This study aims to examine the effect of audit quality, debt default, and corporate growth on acceptance of going concern audit opinion. This study is motivated by the fact that investors rely heavily on audit opinions given by auditors to make investment decisions. The population in this study are 35 companies engaged in the manufacturing industry listed on the Indonesia Stock Exchange (IDX) in the year 2009 - 2011. The study sample amounted to 32 companies. This study uses secondary data in the form of annual reports during the period 2009 - 2011 obtained from the Indonesia Stock Exchange (IDX) and Indonesian Capital Market Directory (ICMD). The variables in this study are going concern audit opinion, audit quality, debt default, and company growth. The result of the research shows that audit quality does not have an effect on going concern audit opinion while debt default and corporate growth have an effect on going concern audit opinion.